MEMAHAMI GANGGUAN BERBICARA CADEL DAN DAMPAKNYA PADA KOMUNIKASI - Desy Wulandari; Meilan Arsanti (UNIVERSITAS SERAMBI MEKKAH, 2024)
A lisp is a speech disorder that makes it difficult for a person to pronounce words fluently, especially the